2012
DOI: 10.1089/neu.2011.2084
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Impairments in Relation to General Cognitive Deficits, Injury Severity, and Prefrontal Lesions in Traumatic Brain Injury Patients

Abstract: Impairments in social behavior are frequently found in moderate to severe traumatic brain injury (TBI) patients and are associated with an unfavorable outcome with regard to return to work and social reintegration. Neuropsychological tests measuring aspects of social cognition are thought to be sensitive to these problems. However, little is known about the effect of general cognitive problems on these tests, nor about their sensitivity to injury severity and frontal lesions. In the present study 28 chronic TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 85 publications
11
116
0
1
Order By: Relevance
“…According to the studies, individuals with TBI were impaired in mentalistic inferences and faux pas stories (4,39,45,46,50,53,54). In some studies, TBI persons were not impaired in the nonmental/physical/logical inferences, no faux pas stories, and logical stories (4,27,36,39,46).…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, individuals with TBI were impaired in mentalistic inferences and faux pas stories (4,39,45,46,50,53,54). In some studies, TBI persons were not impaired in the nonmental/physical/logical inferences, no faux pas stories, and logical stories (4,27,36,39,46).…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairments are frequent in both patients with TBI and animal models (Spikman et al, 2012), and Ab levels were found to be elevated in CSF and postmortem brain samples from patient with TBI (Uryu et al, 2007). Hyperactivity of GSK-3 has been implicated in the pathogenesis of AD (Hooper et al, 2008), an idea supported by the fact that lithium treatment produces many benefits in various A proposed model to demonstrate the molecular actions of lithium and VPA in preclinical models of cerebral ischemia.…”
Section: B Tbimentioning
confidence: 99%
“…Croker & McDonald, 2005;Babbage et al, 2011, Ietswaart, Milders, Crawford, Currie & Scott, 2008Spikman, Timmerman, Milders, Veenstra & van der Naalt, 2012;Williams & Wood, 2010). Understanding other people's intentions and beliefs, also referred to as theory of mind (ToM), can also be impaired following TBI (Bibby & McDonald, 2005;Bivona et al, 2014;Geraci, Surian, Ferraro, Cantagallo, 2010;Havet-Thomassin, Allain, Etcharry-Bouyx & Le Gall, 2005;McLellan & Mckinlay, 2013;Milders, Ietswaart, Crawford & Currie, 2006, 2012Muller, Simion, Reviriego, Galera, Mazaux, Barat & Joseph, 2010;Spikman et al, 2012). Selecting appropriate social behaviour in response to the context would rely on adequate executive functioning (Shany-Ur & Rankin, 2013), in particular, flexibility to adjust behaviour in accordance with the situation and inhibition to suppress initial, and possibly inappropriate, responses.…”
Section: Introductionmentioning
confidence: 99%